Difundindo e popularizando a ciência na UNESP: interação entre pós-graduação e ensino médio: Reprodução de A a Z - Rocha, Lucia Regina Machado da [UNESP]; Nishida, Silvia Mitiko [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The project untitled “Spreading Design and popularizing Science at UNESP: reproduction from A to Z “has the aims to contribute to improve of quality of primary and secondary education in public schools from Botucatu city, São Paulo and region. Alternative program activities of teaching science and biology (such as laboratory practices, recreational models, plays, games, games, music and videos) at schools of public schools. Creates opportunities for technical and academic training teachers and school students from public schools. This project contributes to didactic training of undergraduates and postgraduates students (Msc and PhD) and strengthens the link between university and basic education in Science and Biology. Every year in January ministers a course for the Postgraduate General and Applied Biology Program entitled Spreading Design and popularizing Science at UNESP: reproduction A to Z which consists of two parts, the first is the preparation of university students to develop summer course reproduction from A to Z for public school students. The second part of the course is running together students from public schools to develop activities such as laboratory practices, theater, music and games. We've had about 200 students, students who excel participated in research activities at the laboratories of the UNESP Biosciences Institute, through the activity called for "New Talent Program" with scholarship. In 2014 we had 18 students in the program and 6 students enrolled in courses at UNESP.

O Projeto Difundindo e Popularizando a Ciência na UNESP: reprodução de A a Z visa contribuir com a melhoria na qualidade do ensino fundamental e médio nas escolas da rede pública. Programa atividades alternativas de ensino de Ciências e Biologia (como práticas laboratoriais, modelos lúdicos, peças de teatro, brincadeiras, jogos, músicas e vídeos) nas escolas da rede pública de ensino. Gera oportunidades de formação técnicoacadêmica para professores de ensino fundamental e médio e a alunos de ensino médio da rede pública. Assim como cria oportunidades de formação didática a alunos de pós-graduação. Essas atividades estreitam os laços entre universidade, escola pública de ensino fundamental e médio e população em geral. Anualmente em janeiro ministramos uma disciplina para o programa de Pós-graduação Biologia Geral e Aplicada intitulada Difundindo e Popularizando a Ciência na UNESP: reprodução de A a Z que consta de duas partes a primeira e a preparação dos alunos da pós-graduação para desenvolverem o curso de férias Reprodução de A a Z para alunos da rede pública. A segunda parte da disciplina é a execução do curso de férias juntos aos alunos da rede pública desenvolvendo atividades tais como práticas laboratoriais ,teatro , musica e jogos. Já tivemos aproximadamente 200 alunos, Os alunos que se destacam participaram de atividades de pesquisa junto a laboratórios do Instituto de Biociências da UNESP, através da atividade denominada de “Programa novos talentos” com bolsa de Iniciação cientifica Junior. Em 2014 tivemos 18 alunos nesse programa e 6 alunos ingressaram nos cursos da UNESP.
Keywords: Reproduction; Basic education; Reprodução; Ensino fundamental e médio; Material didático